Between destruction and protection: the case of the Australian rock art sites - González Zarandona, José Antonio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Can heritage be practiced and thought outside the binary of exaltation vs. denigration? To answer this question posed by the editors, this paper will analyse the destruction and protection of Indigenous heritage sites in Australia, where the destruction of significant cultural heritage sites, mainly Indigenous heritage sites, is the result of biased and outdated practice of cultural heritage that divides Indigenous heritage (prior 1788) from Australian heritage (after 1788). This rift has caused an immense damage to Indigenous heritage around the country as it shows how in Australia heritage is practiced and thought outside the dualism of celebration versus destruction. In this paper, I will show how the destruction of Indigenous rock art sites has been a constant in the 20th and 21st century and how this destruction has been framed in media as a result of vandalism. By arguing that this framing is perpetuating the dualism of celebration versus destruction, I suggest that we can move out of this binary by considering the concept of iconoclasm to go beyond this dualism.
Keywords: rock art; Australia; destruction; heritage; iconoclasm